Dry machining technology to the capability of tin coated carbide tool performance on alloy steel TEW 6582 the lathe process - Napid, Suhardi; Haris Nasution, Abdul; R. Harahap, Muksin; Hasibuan, Abdurrozzaq; Sri Poneni, Istu (International Journal of Engineering and Technology, 2018)
The objective of research is to study the capability of TEW 6582 steel material with dry machining technology. The re-search determine cutting conditions for the purpose of studying the results of tool ability after the completion of the ma-chining process on the growth of tool wear, tool wear rate, cutting temperature, tool life. The experimental on wet and dry machining each have 27 specimens that is 9 different cutting conditions by three variations of VB tool wear using optical microscope. To study on the growth of tool wear is used by SEM. The data from the experiment were processed and ana-lysed by the standard Taguchi method L9 (34). The growth of TIN carbide tool wear is influenced by cutting speed, cutting depth, feeding, cutting temperature and tool geometry. Optimum cutting conditions with dry machining at 200 m/min cut-ting speed, 0.1 mm cutting depth, 0.15 mm/rev feeding and 6o cutting angle which gives the tool life T = 2456 sec. While cutting conditions on wet machining obtained the tool life T = 2591 seconds. Differentiation of tool life in dry machining and wet machining is not significant. Thus dry machining is a good choice that can be realized in the metal cutting indus-try.Â Â